IMPLICATIONS OF LABELLING RADICALISM ON INDONESIA POLITICS AND DEMOCRACY - Mochammad Fauzen (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Abstract: The words radical and radicalism have commonly been used in social media nowadays and generally associated with Islam leading to a negative perspective of Islam. As a result, Islam is labelled as a radical religion which allows intolerance, and violence. In Indonesia, such a negative labelling has occurred not only to Islam as a (peaceful) religion but also to a certain person or group who are considered by the government buzzers or supporters as the opposition of the regime. Those who criticize the government are often categorized as radicals, anti-Pancasila and pro-Islamic state. In fact, the majority of Indonesian people including Muslims have agreed that Pancasila is the national legal basis for all. Such a labelling has led to polarization among Indonesian people and could lead to the division of Indonesia. Criticism seems to have no place in this country. This paper explains about the terms of radical and radicalism both in general and in the context of Indonesia. Furthermore, the writer will discuss about the use of radical and radicalism labels to a certain person or group and its implications for Indonesia politics and democracy. Finally, the writer also offers several solutions to avoid polarization and prevent this nation from disunity.Keywords: Labelling Radicalism, Radicals, Radicalism, Politics, Democracy